LEVELS OF COMPASSION FATIGUE AND ITS RELATION TO PSYCHOLOGICAL DISTRESS AMONG HELPING PROFESSIONALS - adminojs, adminojs; Mary Scarlette G. Auguis, Angie Ayne R. Gako, Cathlene Kate P. Abayata, Fritzie Ann N. Bartolabac, Shamen G. Sanico, and Ronald C. Yrog-Irog, (Chelonian Research Foundation, 2024)
Abstract - The job of helping professionals is emotionally and physically demanding by nature. They are more likely to experience the negative impacts of helping, such as compassion fatigue and psychological distress. The research study analyzed the demographic profile of 100 helping professionals from the selected institutions within Cebu City. Demographics include sex, age, job, and length of service of the helping professional. The levels of compassion fatigue and psychological distress were also assessed. Finally, the study investigated the relationship between demographic profile, compassion fatigue, and psychological distress. A quantitative study was used, and the researchers utilized a descriptive correlational survey research design to describe the relationship between compassion fatigue and psychological distress. The study used the Quota sampling method to collect data from 100 helping professionals in selected institutions from Cebu City. The study's results have shown a significant relationship between CF and PD with a correlation coefficient of ρ = 0.760 and p-value of 0.000, indicating a strong positive relationship between the two variables. However, based on the results, the correlation between CF and demographic profile was insignificant, indicating that age, sex, length of service, and specific helping profession don't influence a helping professional's risk of experiencing CF. The same was found true between PD and demographic profiles, indicating that the respondent's demographic profile does not affect their level of psychological distress. At the end of the study, the researchers proposed a program to support helping professionals.